PROFESIONALISME PEGAWAI KECAMATAN DALAM PELAYANAN KARTU TANDA PENDUDUK ELEKTRONIK - Afmi Apriliani; Euis Salbiah; Siti Wulandari (Jurnal Governansi, 2023)
One of the big challenges for the government, especially local governments in public services, is to display professional behaviour, as well as a high work ethic. The purpose of this study is to determine the level of professionalism shown by service employees. E-KTP (Electronic Identity Card). Population administration and civil registration services in Caringin District, Bogor Regency. This study uses a descriptive method with a quantitative approach. With respondents totalling 20 employees of the -district office, using probability sampling techniques, collecting data through library research, observation, interviews and questionnaires. The results showed that the professionalism of employees at the Caringin District office, Bogor Regency, was seen from competence, effectiveness, efficiency and responsibility in the implementation of services that were good, but there were still several dimensions that were still below the average outcome value of variables, namely the competency dimension with an average value average of 4.11, dimensions of effectiveness with an average value of 4.15, dimensions of efficiency with an average value of 4.12 and dimensions of responsibility with an average score of 4.12. Suggestions in this study need to increase the capacity of employees through job training and seminars in order to increase the knowledge and abilities of officers in providing services.